Comparison of Dual Therapy, Rifaximin plus Lactulose with Monothrapy, Lactulose Alone in the Treatment of Portosystemic Encephalopathy - Hyder Wajid Abbasi, Mashood Ali, Irfan Younus, Furqan Tahir, Adnan Qadir, Talha Firoz, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the efficacy of dual therapy (rifaximin and lactulose) and lactulose monotherapy in the treatment of porto-systemic encephalopathy. Study Design: Randomized control trial. Place and Duration of Study: Department of Gastroenterology, PIMS Hospital, Islamabad from 1st July 2020 to 31st December 2020. Methodology: One hundred and fifty patients of both genders age ranges from 18-65 years with liver cirrhosis having hepatic encephalopathy grade II or above were included. They were divided in two groups; each group comprised 75 patients. Group A took lactulose and rifaximin, while lactulose alone was given to Group B. All patients were monitored for 5 days on the basis of Child Pugh Criteria. Results: The mean age was 40.02+24.4 years. One hundred twenty six (85.1%) of patients were above 50 years. Males were 60%, majority of patients were from the emergency department, while 17 were from OPD. HCV was identified as the major cause of cirrhosis (72.6%), while HBV (14.6%), alcohol (4%) and others (8.6%) contributed nominally. Constipation was major precipitating factor in 83 patients while sepsis and UGI Bleed was culprit in 31 and 19 patients respectively. Sixty patients (80%) of group A of both genders showed improvement in five days, while 42 patients (56%) of group B showed improvement in the same period of time (p=0.006). It was found more in males and elder patients. Practical implication: Dual therapy will reduce the morbidity, hospital stay and cost of treatment. It may also help in making local guidelines for treatment of hepatic encephalopathy. Conclusion: Rifaximin plus lactulose therapy was far superior to lactulose monotherapy in every age group and either gender. Keywords: Porto systemic encephalopathy, Decompensated chronic liver disease, Rifaximin lactulose therapy, Lactulose monotherapy